Compared the physiological response of two petroleum tolerant-contrasting plants to petroleum stress. Issue 10 (24th August 2018) - Ma, Hui; Wang, Ao; Zhang, Menghua; Li, Haoge; Du, Sisi; Bai, Liping; Chen, Shuisen; Zhong, Ming
ABSTRACT: Petroleum not only benefits the world economy but also contaminates the soil. In order to select the plants tolerant to petroleum, the physiological response of two petroleum tolerant-contrasting plants, Mirabilis jalapa and Orychophragmus violace, were investigated in variation of petroleum-contaminated soils (0, 5, 10, 20, and 40 g petroleum per kg soil) for 120 d. Petroleum degradation rate, seeds germination rate, free proline, and superoxide dismutase and peroxidase activities of M. jalapa were higher than that of O. violace under petroleum stress. However, the decrease rate of soluble protein, plant height, chlorophyll, and root fresh weight was greater in O. violace as compared to M. jalapa. Pearson correlation coefficient analysis was conducted, which indicated that the higher tolerance of M. jalapa was correlated with the higher level of free proline and antioxidative enzyme activities. Besides, the 10 g petroleum per kg soil may be appropriate for petroleum-tolerant plants selection, in which petroleum significantly restrain growth in O. violace but not in M. jalapa.